Legal Protection On Children As Witness Of Victims In Criminal Justice - Ria Latifah; Gunarto Gunarto (Universitas Islam Sultan Agung, 2020)
Indonesia's legal protection is inadequate for children as witnesses of victims of criminal acts of decency in the criminal justice process. The objectives of the research include: To analyze the implementation of legal protection for children as witnesses of victims of crime of decency in the criminal justice process at the Kendal District Court, To analyze the treatment of children as witnesses to victims of criminal acts of decency during the criminal justice process at the Kendal District Court and for analyzing the obstacles and solutions in providing legal protection to children as witnesses of victims of crime of decency in the criminal justice process at the Kendal District Court. In this study, a sociological juridical approach is used, an approach used in dealing with problems discussed based on applicable regulations and then linked to the reality that occurs in the community. Based on the research, the conclusion is: Implementation of Legal Protection for Children as Witnesses to Victims of Crime of Decency in the Criminal Court Process against children as victims of decency crimes in the form of legal protection in the form of: Restitution and Compensation, Counseling, Medical Assistance, Legal Aid and Information Providing. Treatment of Children as Witnesses to Victims of Criminal Actions of Decency during the Criminal Court Process Law enforcement officials still treat women victims of child sexual abuse as objects, not subjects that must be heard and respected for their legal rights and Constraints and Solutions in the Kendal District Court. The victim feels traumatized as a result of this case in providing testimony at the trial and the solution and solution to these obstacles is that victims of criminal acts of sexual immorality continue to be given support from both family and community.